2017
DOI: 10.1371/journal.pone.0177665
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biological sealants and adhesive treatments on matrix metalloproteinase expression during renal injury healing

Abstract: BackgroundRenal injuries are relatively common in cases of abdominal trauma. Adhesives and sealants can be used to repair and preserve damaged organs. Using a rat model, this study explores the activity of different matrix metalloproteinases (MMP) during the healing of renal injuries treated by two biological adhesives (TachoSil and GelitaSpon) and a new synthetic elastic cyanoacrylate (Adhflex).MethodsRenal traumatic injuries were experimentally induced in 90 male Wistar rats by a Stiefel Biopsy Punch in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…increased in IL-1 β treated hTDCs but, when cells were exposed to PEMF the MMPs levels decreased. The expression of MMPs, enzymes implicated in cell responses to the environmental cues, including cell proliferation, migration, differentiation and in the dynamic process of ECM turnover, with relevant implications in the inflammatory and remodeling phases of healing [33] , suggest that PEMF actuation can modify hTDCs behavior, decreasing the expression of MMPs associated to collagen degradation, which may contribute to inflammatory pain and tendon lesions. As cytoskeleton changes often precede MMP modulation during tissue remodeling, actin dynamics might be linked to the expression of MMP genes [34] .…”
Section: Discussionmentioning
confidence: 99%
“…increased in IL-1 β treated hTDCs but, when cells were exposed to PEMF the MMPs levels decreased. The expression of MMPs, enzymes implicated in cell responses to the environmental cues, including cell proliferation, migration, differentiation and in the dynamic process of ECM turnover, with relevant implications in the inflammatory and remodeling phases of healing [33] , suggest that PEMF actuation can modify hTDCs behavior, decreasing the expression of MMPs associated to collagen degradation, which may contribute to inflammatory pain and tendon lesions. As cytoskeleton changes often precede MMP modulation during tissue remodeling, actin dynamics might be linked to the expression of MMP genes [34] .…”
Section: Discussionmentioning
confidence: 99%
“…In groups 3 and 4 (kidney omentum repair groups), transpositioned autologous omentum was used without primary sutures on the injured renal tissue for repair. We preferred the time of sacri ce as the 18 th postoperative day, according to the study of Miguel et al (14) which reported that posttraumatic necrosis in the tissue disappeared on the 18 th day. In that study, after this period, collagen maturation took place in the renal capsule and connective tissue at the edges of the wound were contracted (14).…”
Section: Methodsmentioning
confidence: 99%
“…We preferred the time of sacri ce as the 18 th postoperative day, according to the study of Miguel et al (14) which reported that posttraumatic necrosis in the tissue disappeared on the 18 th day. In that study, after this period, collagen maturation took place in the renal capsule and connective tissue at the edges of the wound were contracted (14). The summary of the procedures performed in the study groups are outlined in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental studies provide evidence that glucocorticoids mediated the transcriptional suppression of cytokine-induced MMP-9 expression in rat mesangial cells [41, 42]. A recent article exploring the effect of biological sealants and adhesive treatments on MMP expression during kidney damage healing found that the expression of collagenases (MMP-1, MMP-8, and MMP-13) and subsequently the expression of gelatinases (MMP-2 and MMP-9) occur at different tested time periods [43]. This overexpression of metalloproteinases at the early healing period obviously does not influence the final kidney repair [43].…”
Section: Collagenases (Mmp-1 Mmp-8 Mmp-13 and Mmp-18)mentioning
confidence: 99%
“…Different time manner was specifically prominent with maximal MMP-8 and MMP-9 expression after 2 days of injury in healing of the wound. In contrast, the MMP-2 expression peaked after 6 days of kidney traumatic injury [43]. …”
Section: Gelatinases (Mmp-2 Mmp-9)mentioning
confidence: 99%